1996
DOI: 10.1128/mcb.16.12.7072
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive Activation of the RON Gene Promotes Invasive Growth but Not Transformation

Abstract: MET, RON, and SEA are members of a gene family encoding tyrosine kinase receptors with distinctive properties. Besides mediating growth, they control cell dissociation, motility ("scattering"), and formation of branching tubules. While there are transforming counterparts of MET and SEA, no oncogenic forms of RON have yet been identified. A chimeric Tpr-Ron, mimicking the oncogenic form of Met (Tpr-Met) was generated to investigate its transforming potential. For comparison, a chimeric Tpr-Sea was also construc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
70
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(82 citation statements)
references
References 54 publications
12
70
0
Order By: Relevance
“…Ron is less e cient than Met as a kinase (Santoro et al, 1996), thus, the formation of complexes Met/Ron, resulting in a more e cient Ron transphosphorylation by Met, may lead to a more sustained signal than that induced by the Ron/Ron homodimer. Di erent subsets of transducers may be engaged by the heterodimeric receptor complex, providing a mechanism of ®ne tuning of signal transduction.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ron is less e cient than Met as a kinase (Santoro et al, 1996), thus, the formation of complexes Met/Ron, resulting in a more e cient Ron transphosphorylation by Met, may lead to a more sustained signal than that induced by the Ron/Ron homodimer. Di erent subsets of transducers may be engaged by the heterodimeric receptor complex, providing a mechanism of ®ne tuning of signal transduction.…”
Section: Discussionmentioning
confidence: 99%
“…The response to HGF and MSP through the activation of Met and Ron is mediated by the same pathways, mainly by Ras and by PI-3 Kinase (Wang et al, 1996;Bardelli et al, 1999). Met can regulate growth and transformation by activating the MAP kinase cascade through Grb2/Sos/Ras complex whereas the Ron pathway is directed more towards cellular movement and matrix invasion (Santoro et al, 1996;Wang et al, 1997). When Met and Ron receptors are co-expressed, the formation of heterodimers may balance the activation of Ras and PI-3 kinase pathways.…”
Section: Discussionmentioning
confidence: 99%
“…RON belongs to a tyrosine kinase gene family whose prototype is MET. A number of reports suggest that members of this family are involved in the progression of cancer: (I) germline and somatic missense mutations in the tyrosine kinase domain of MET are involved in papillary renal carcinogenesis (Schmidt et al, 1997); (II) Met is overexpressed in some carcinoma types at advanced stages (Di Renzo et al, 1995); (III) activation of the Met receptor via an experimental autocrine circuit (Rong et al, 1994) or by rearrangement (Giordano et al, 1997) confers metastatic properties; (IV) all the known members of the family stimulate invasion in vitro (Giordano et al, 1993;Medico et al, 1996); (V) although no transforming counterpart of the RON gene has been identi®ed so far, constitutive activation of the Ron kinase elicits a motogenic-invasive phenotype Santoro et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the cDNA encoding wtRON or RONDp165 does not have cell-transforming activity when introduced into rodent fibroblasts Santoro et al, 1996). To determine if cloned RON variants have the ability to transform cells in vitro, the focus-forming assay was performed using NIH3T3 cells as the indicator.…”
Section: Ron Variant-mediated In Vitro Cell-transforming Activities Imentioning
confidence: 99%